A poetização do cotidiano na poesia de Manuel Bandeira - Endo, Jucimeire Ramos de Souza (2006)
The purpose of this Master dissertation is to apprehend the process of poetic construction in Manuel Bandeira s Libertinagem s poems. The selected poems are Evocação do Recife , Poema tirado de um notícia de jornal and Poema de Finados , which were put together, rounded up in three thematic nucleus: childhood, social conscience and death. In its analysis, this study tries to explore the elements that led to lyric simplicity, the thematic of colloquialism, the prosaic, childhood reminiscences and death. It starts with the everyday life thematic, in which the self lyric retrieves its richest poetic element from commonplace and real life situations. Then it asks the questions: What formal or structural elements work as poetic resources to translate everyday life? How the hybridization of the lyric gender produce in Manuel Bandeira s poetry an effect that describes a peculiar treatment of his poetry? Trying to meet this poetic proposal, it was used as theoretical bases, Victor Chklovski, Roman Jakobson, Iuri Tynianov, Octavio Paz and Hugo Friedrich s conceptions. Among other aspects, were studied the irregular rhythmic movements, random or absent rhymes, multiplicity of sounds, arbitrary cut, proselike approach, generation of images particularities of poetic language. As a conclusion, the study suggests that when Manuel Bandeira introduced in his poetry everyday life elements, colloquial language and characteristics of narrative gender, for example, he broke the laws of the traditional poetic form and produced an hybrid poetic, which allowed him to go free and led him to a new form of poetic: the everyday life poetic